Applying Alter Ego Rule in Parent and Subsidiary Corporations: A Comparative Study of American Law, Imamiyah Jurisprudence and Law of Iran - gholamnabi chekab; Majiid Banaii Oskoii; SEYYED MOHAMMAD MOSAVI (پژوهش تطبیقی حقوق اسلام و غرب, 2020)
If two corporations are related and affiliated through management and economic circles, one is called the parent and the other is the subsidiary. This affiliation will, in most cases, result in the complete domination and control of the parent over the subsidiary and thus abuse its template. Now, given the acceptance of the principle of limited liability in corporate law, can the legal practices and actions created be attributed to the parent company as the controller of the legal relationship (between the subsidiary and third parties)? The US legal system, by resorting to the Alter Ego rule, has prevented such an abuse. The Alter Ego refers to the conditions that the courts exercise on the basis of Justice and Equity and thereby treat the parent company as the proprietor of the company or the real party to the benefit against good faith third parties. The basic conditions for applying this rule can be effective real ownership and control of the Alter Ego (the parent company) over the actions of the subsidiary, unity of interest and ownership between the two companies and unjustified actions of parent company. In the Iranian legal system, there is no explicit regulation in Trade Code in this regard. There is no specific solution in the case law as well. But it seems that by taking advantage of capacities of Imamiyah jurisprudence and domestic law such as The Swindle Rule, theRule of No Damage, the Theory of Agency, the Theory of Relative Independence of the Legal Personalityand other principles, this rule can be applied.